miR-187 inhibits the growth of cervical cancer cells by targeting FGF9 - Liang, Hua (Oncol Rep, 2017)
MicroRNAs (miRNAs) are a cluster of short non-coding RNAs playing critical roles in human cancers. miR-187 was recently found to be a novel cancer-related microRNA. However, the expression and function of miR-187 in cervical cancer have not been investigated. In this study, we found that miR-187 level was decreased in cervical cancer tissues and cell lines. Patients with low level of miR-187 had significantly decreased rate of overall survival (OS) and progression-free survival (DFS). miR-187 overexpression inhibited proliferation and promoted apoptosis of cervical cancer cells, whereas miR-187 knockdown promoted proliferation and inhibited apoptosis of cervical cancer cells. Forced expression of miR-187 inhibited the subcutaneous growth of cervical cancer cells in nude mice. Furthermore, FGF9 was found to be the downstream target of miR-187 in cervical cancer cells. Importantly, targeting FGF9 was required for miR-187 exerting its tumor suppressive roles in cervical cancer cells.